The Victorian church ; pt 1 - Chadwick, Owen, 1916- (London, UK Adam and Charles Black, 1971)
Contents : v. 1 : i. Church in danger ; ii. The Whig reformof the church ; iii. The Oxford movement ; iv. Lord John Russell ; v. Religion and the labourer ; vi. The dissenters ; vii ; The Church of England 1853-60 ; viii. Unsettlement of faith. Includes bibliographical references and index.
Keywords: Church history -- 19th century